ANALISIS KEUNTUNGAN, KELAYAKAN USAHA DAN TITIK IMPAS USAHATANI PADI SAWAH DI DESA MIAU BARU KECAMATAN KONGBENG KABUPATEN KUTAI TIMUR - Rusmiyati Rusmiyati (Jurnal Magrobis, 2018)
This study aims to determine the amount of profit, business feasibility and the break even point of paddy field farming in Miau Baru Village Kongbeng District East Kutai Regency. Research time for 4 months, starting from January until April 2017. Determination of respondents done by way of purposive (purpossive), the number of farmers respondents taken in this study for 77 respondents who use the complete fertilization of 514 rice farmers. Data collection methods used in this study are observation, direct interview and literature study. The analysis is profit analysis, feasibility analysis of farming and break event point analysis. The result showed that average production of paddy field was 2,857,714 kg / ha per respondents per planting period, mean while total cost of farmer of respondents average Rp 11.042.746,78 / ha per responden every planting period and profit of rice farming in Desa Miau Baru District Kongbeng East Kutai Regency is Rp. 17,534,396,22 / ha per farmer with R / C value = 2,588 showed that R/C> 1, farming profitable (additional benefit or acceptance greater than additional cost), while from result of analysis of B / C ratio is equal to 1,588 indicates that B/C> 1 means farming is feasible to run. Keywords: Benefit, Feasibility, Break Even Point